If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -97 = 4x + -13 Reorder the terms: -97 + 7x = 4x + -13 Reorder the terms: -97 + 7x = -13 + 4x Solving -97 + 7x = -13 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -97 + 7x + -4x = -13 + 4x + -4x Combine like terms: 7x + -4x = 3x -97 + 3x = -13 + 4x + -4x Combine like terms: 4x + -4x = 0 -97 + 3x = -13 + 0 -97 + 3x = -13 Add '97' to each side of the equation. -97 + 97 + 3x = -13 + 97 Combine like terms: -97 + 97 = 0 0 + 3x = -13 + 97 3x = -13 + 97 Combine like terms: -13 + 97 = 84 3x = 84 Divide each side by '3'. x = 28 Simplifying x = 28
| 211-4x=32x+19 | | logy=1.6 | | 2x+x+400+2x=5000 | | x(x-20)=525 | | 75-2x=2x+19 | | -16-2x=-10x | | 3(x-2)-5(3-4x)=29-2x | | p^2-20-8p=0 | | (-2.6)+7=7+(-2.6) | | 20+8p=p^2 | | 9b+36=b^2 | | 6-(-15)= | | 3x=15y | | (-3y^2)(2xy)(-x)= | | 16X^3-24x^2-12x-14=0 | | (-3y^2)(2xy)= | | 2*(2+2)/2= | | 8x^2=7x | | f^2=10f-16 | | a^2+8a-9=0 | | (c-6)(c-3)=23 | | 5w*u*u= | | x(x-1)=x | | a(a-5)= | | 7x-14=48-14x-28 | | 2x+4=36-2x | | 2(x-2)=3(x+3) | | 7x-3y+14=0 | | 11(4-6(40))+5(13(40)+1)=9 | | 4x^2-17x+15=-5x+10 | | -4x+12y-6=0 | | 2x+6y-8=0 |